International consensus guidelines for phosphoglucomutase 1 deficiency (PGM1-CDG) - Altassan, Ruqaiah (2021)
P. W. is supported by the Clinical Research Fund, University Hospitals Leuven, Leuven, Belgium. This work is partially funded by the grant titled Frontiers in Congenital Disorders of Glycosylation (1U54NS115198-01) from the National Institute of Neurological Diseases and Stroke (NINDS), the National Center for Advancing Translational Sciences (NCATS), and the Rare Disorders Consortium Research Network (RDCRN) (E. M., K. R., C. F., H. F., C. L., and A. E.)